The impact of dysbiosis in oropharyngeal and gut microbiota on systemic inflammatory response and short-term prognosis in acute ischemic stroke with preceding infection - He, Qiuxing; Li, Guoshun; Zhao, Jiasheng; Zhu, Huishan; Mo, Huanhao; Xiong, Zhanshi; Zhao, Zhan; Chen, Jingyi; Ning, Weimin (Frontiers in Microbiology, 2024)
Background: Stroke is a devastating disease and ranks as the second leading cause of death and disability globally. Several studies have shown that preceding infection (PI) of upper respiratory tract are strongly associated with acute ischemic stroke (AIS).However, the clinical implications and underlying pathological mechanisms remain unclear. Methods: In this study, 16S rRNA gene sequencing was employed to compare the structural characteristics of oropharyngeal and gut microbiota in AIS patients with or without PI and normal controls (NCs) (30 cases each), and systemic inflammatory markers were detected to explore the relationship between upper respiratory tract infections (URTIs) and subsequent stroke severity and functional outcome and the potential mechanism. Results: We found that patients with AIS-PI exhibited elevated serum WBC, NE, CRP, and Hcy levels, as well as a higher 90-day mRS score. Oropharyngeal and gut microbiota analysis showed that AIS and AIS-PI patients exhibited increased microbial richness in sequence. Principal coordinate analysis of the microbiota demonstrated significant differences in microbiota composition among the three groups. In AIS-PI patients, Megamonas, Megasphaera, Ruminococcaceae UCG 004, Rothia and Streptococcus were significantly enriched in the gut. Opportunistic pathogens, including Thermus, uncultured Veillonella sp., and Oribacterium sinu, were found to be significantly enriched in the oropharynx. The dysregulated microbiota were positively correlated with systemic inflammatory markers, stroke severity, and poor prognosis. In contrast, short-chain fatty acid-producing bacteria Eisenbergiella, bacterium NLAE, Fusicatenibacter, Ruminococcaceae and Faecalibacterium were enriched in NCs. Their abundances were negatively correlated with systemic inflammatory markers, stroke severity and poor prognosis. Conclusion: Our findings suggest that PIs of the upper respiratory tract may contribute to poor short-term functional outcome in AIS patients by causing disturbance of the oropharyngeal and gut microbiota and promoting elevated systemic inflammation levels.